Functional and age structure of oak stands in Eastern Polissia and their productivity - Rumіantsev, M. Н. (Forestry and Forest Melioration, 2020)
Introduction The structural analysis of forests serves as a basis when developing activities aimed at ensuring a sustainable multifunctional usage of forest ecosystems with their functional, species and age structures taken into account. To identify a regime of forest use and provide efficient management in oak forests, it is necessary to define their functional purpose. Materials and Methods The object of the study involves oak stands of different origins (vegetative, natural seed and planted seed stands) in Eastern Polissia іn all categories of forests of the total area of 41 thousand hectares. The forest management data (subcompartment database) were the basis for calculations. The forests were divided into categories in accordance with The Procedure of Division of Forests on Categories and Determination of Protective forest Areas. Results The study showed that a composition of the main forest-forming species in Eastern Polissia forests is rather diverse and includes 43 tree species. Oak stands (Quercus robur L.) occupy 10% or 41 thousand hectares of the total area covered with forest vegetation. According to the findings, exploitable forests make the largest part of oak forests in Eastern Polissia, namely 58.0% (23,785 hectares). Far less of the total area (27.2% or 11,133 hectares) is occupied by forests with the stands of conservational, scientific, historical and cultural significance. Recreational forests and protective forests cover 8.4% (3,439 hectares) and 6.4% (2,634 hectares) respectively. A distribution of the total stock of oak forests by the forest categories is about the same as by their area. The oak stands were found to have an imbalanced age structure in all forest categories. At that, middle-aged and premature stands significantly predominate, mature and overmature stands make a considerable proportion, and young stands have a minor part. On assigning each individual forest site of oak stands to a certain forest category, it is necessary to establish a proper regime of forest management, appropriate felling, in particular. The yield tables and tables of productivity dynamics have been developed for the oak stands in terms of their origin and forest categories. All these tables can be used to predict the growth of the stands as well as to determine a range of forestry operations and their priority. Conclusions To carry out effective forest management in the oak forests within Eastern Polissia, in particular, it is necessary to improve their age structure taking into account their functional purpose defined by the forest categories they are in. Результати досліджень щодо особливостей росту дубових насаджень бажано в подальшому використати при обґрунтуванні й уточненні нових віків стиглості та внесенні відповідних змін у нормативно-правові акти, що регулюють лісогосподарську діяльність в дубових лісах. It is advisable to use the findings regarding features of oak stands growth in the future when grounding and refining new maturity ages as well as when amending regulatory materials for forest fund accounting, design and planning of forestry operations in oak forests. 1 Fig., 6 Tables, 11 Refs. Key words: Ouercus robur L., forest categories, stand origin, age groups, yield tables.